Maintaining oral hydration in older adults in surgical wards: a best practice implementation project. Issue 1 (16th March 2022) - Seah, Kwang Hui; Low, Amanda Pei Shan; Low, Jian Ying; Luk, Grace Kar Sin; Chia, Hui Xian; Goh, Mien Li
ABSTRACT: Introduction and aim: Oral hydration is essential in older adults as poor hydration can complicate existing medical conditions and increase morbidity. Older adults in surgical wards are at risk of dehydration due to insufficient fluid consumption. The aim of this project is to ensure patients aged 65 years and above are adequately hydrated. Methods: The current project was conducted over 7 months from February to August 2019 and involved pre and postimplementation audits to ensure compliance with best practice. The Joanna Briggs Institute Practical Application of Clinical Evidence System and the Getting Research into Practice tools were used as a guide. Audits were conducted at four surgical wards with a sample of 42 patients at each audit. The measures implemented include educating nurses on the importance of oral hydration in older adult patients and labelling water jugs to encourage fluid intake among these patients. Results: Nurses' compliance in monitoring older adult patients' daily fluid intake increased from 5 to 76% at follow-up audit ( P  < 0.05). In addition, the average amount of fluid consumed over 3 days increased from 858.23 to 1037.50 ml. Conclusion: This project demonstrated a significant increase in oral fluid intake among older adult patients during hospitalization and their understanding of adequate fluid intake. Nurses play an important role in ensuring adequate amounts of daily fluid intake by these patients.